Grain growth behavior and efficient large scale simulations of recrystallization with the phase-field method - Vondrous, Alexander (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2014)
This book summarizes the found insights of grain growth behavior, of multidimensional decomposition for regular grids to efficiently parallelize computing and how to simulate recrystallization by coupling the finite element method with the phase-field method for microstructure texture analysis. The frame of the book is created by the phase-field method, which is the tool used in this work, to investigate microstructure phenomena.